Entropy production by thermodynamic currents in ambipolar conductors with identical spin dynamics characteristics between holes and electrons. (15th April 2019) - Aktar, Mst. Sanjida; Sakai, Masamichi; Hasegawa, Shigehiko; Nakamura, Osamu; Awano, Hiroyuki
Abstract: We have evaluated the role of spin current in the energy dissipation mechanism in ambipolar conductors with identical spin-related characteristics between holes and electrons. Application of the Gibbs–Duhem relation to ambipolar conductors establishes a thermodynamic relation between the spin-dependent chemical potentials of holes and electrons, inducing an asymmetric spin splitting between the hole and electron chemical potentials. This yields two types of spin relaxation so as to allow the antiparallel spin current, where hole and electron spins flow in the opposite direction, to have a large spin diffusion length, but to retain that of the parallel spin current at a standard value.